E-Comic Oriented to Environmental Care Character Education with Natural Science Content - Ida Ayu Mas Utami Putri; I Made Citra Wibawa (Universitas Pendidikan Ganesha, 2023)
Students need to be more concerned about their environment, which is one of the hot problems in the world of education today. This research aims to develop a comic oriented towards character education that cares about the environment. This type of research is developed using the ADDIE model. The research subjects were two learning material experts and two learning media experts. The trial subjects were two teachers and nine students in small group trials. Data collection methods use observation, interviews, questionnaires, and tests. The data collection instrument is a questionnaire. The techniques used to analyze the data are qualitative and quantitative descriptive analysis and inferential statistics. The research results, the assessment given by learning material experts, were 0.95 (very high). The assessment from learning media experts is 0.92 (very high). The teacher's response was 97.33 (very good). The results of the small group trial were 97.03% (very practical). The t-test results showed a significant difference in students' environmental care attitudes before and after learning using e-comics oriented towards environmental care character education. It was concluded that using e-comic media oriented towards environmentally caring character education effectively increased students' environmentally caring attitudes.